(3GdaQL HYO GdTOIs - (3GdbGVj GdJfhNj , GdeMSf Hf Ydj Hf eMeO Hf CHj Gdage OGhO GdJfhNj GdHUQj, CHh Ydj,J (B384 (3g` s
(3ChdgG (B:s
(3CeG HYO, aEfj deG QCjJ CHfGA GdOfjG eJbdHjf ajgG Hjf NjQ hTQ, hfaY hVQ s
(3BNQgG (B:s
(3MSHc ef MSfg YhGbHog YGbHI GdUHQ eG dgG Keof s
(3QJHg Ydi CQHYI YTQ HGHkGs
(3fSNI NRGFfjI hHChdgG Jedc SfI (B944(3g`s
(3hHgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdCOHs